1982
DOI: 10.1128/aem.43.6.1451-1463.1982
|View full text |Cite
|
Sign up to set email alerts
|

Microbial flora of the mouse ileum mucous layer and epithelial surface

Abstract: We have developed new methods to minimize fluid shear during preparation of specimens for electron microscopy and to retain the mucous blanket that covers the tissue surface of the ileum in mice. We also used general stabilization by nonspecific antibodies to minimize the collapse of the mucous layer during dehydration for electron microscopy. These methods allowed us to visualize the gradual progression of the mucous blanket from a thin diaphanous layer in newborn animals to a very thick (ca. 50-,um), coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…Davis et al [25,26] showed in rats and dogs that the majority of attached SFBs is separated from the gut lumen by a thin film of material which is probably mucus. Rozee et al [27] confirmed this using methods that do not remove the mucous blanket from the mucosal surface.…”
Section: Habitat and Attachmentmentioning
confidence: 94%
“…Davis et al [25,26] showed in rats and dogs that the majority of attached SFBs is separated from the gut lumen by a thin film of material which is probably mucus. Rozee et al [27] confirmed this using methods that do not remove the mucous blanket from the mucosal surface.…”
Section: Habitat and Attachmentmentioning
confidence: 94%
“…This mucus barrier acts as a physical diffusion barrier to large molecular weight toxins and degradative bacterial and digestive enzymes (1). In addition it acts as a free radical scavenger (2,3) and habitat for the endogenous microflora (4)(5)(6). An extensive sloppy mucus layer above the firmly adherent barrier acts as a lubricant to protect the epithelium from shear stress (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of extensive mucous coats on mucosal surfaces has been well described in mammals by a variety of techniques in addition to traditional methods of histological processing using aqueous glutaraldehyde as the fixative (Luchtel, 1978) or with added mucous specific compounds such as ruthenium red (Garland et al, 1979). Other more non-traditional techniques include the use of antibodies (Rozee et al, 1982;Bollard et al, 1986;Cornish et al, 1987) to stabilize the mucus, freeze substitution (Ichikawa et al, 1987), fluorocarbon-osmium fixatives in tracheae and lungs (Thurston et al, 1976;Sims et al, 1991) and microwave fixation (Turner et al, 1990). In addition the characteristics of mucous coats have been described in the oesophagus of the eel (Anguilla anguilla L.) (Humbert et al, 1984), the intestine of the goldfish (Carassius auratus L.) (Caceci, 1984) and on the skin of brown trout (Salmo trutta L.) (Pickering, 1974) and Blenniuspholis L. (Whitear & Mittal, 1984).…”
Section: Introductionmentioning
confidence: 99%